Increasing Social Skill Children Aged 4-5 With the Chaterpillar Game - Anita Damayanti; Nita Priyanti; Iswan Iswan; Lia Rahmawati (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This research is a collaborative classroom action research using the Kemmis and McTaggart models. The research subjects were children aged 4-5 years, totaling 6 children. The object of this research social skills. The data collection method used was observation. The instrument used is an observation guide. Data analysis techniques were carried out descriptively, qualitatively and quantitatively. The success indicator set is that at least 80% of 6 children have social skills with the criteria for developing as expected. At the time of pre-action observation, the initial condition of early childhood social skills in the Buaran area before the action research was still very low where children who could carry out, namely twenty two point five percent. In the first cycle with the achievement of the percentage of fourty seven point five percent until fifty five point five percent.